Emotional Intelligence and Its Impact on Students' Science Learning: A Systematic Literature Review - Kamaluddin Kamaluddin; I Ketut Suma; Ni Ketut Rapi; I Wayan Suastra; Edi Firmansyah; Sofyan Syamratulangi (Universitas Lambung Mangkurat, 2026)
Emotional intelligence has become an important component that influences how well students succeed in learning, including in science. The purpose of this study specifically focuses on the role of emotional intelligence in the context of science learning. This article is a systematic literature review that investigates the relationship between emotional intelligence and science learning. PRISMA guidelines were used in this study to review empirical articles published from 2015 to 2024. In total, 22 articles met the criteria for the systematic literature review. Emotional intelligence acts as an essential basis that connects the emotional side of scientific learning to its cognitive side. Emotional intelligence not only aids in increasing engagement but is also beneficial for enhancing conceptual understanding and can thus be used effectively during the learning process. Studies show that emotional intelligence significantly improves student engagement, critical thinking, and learning outcomes in science learning. This article also discusses the mechanisms of these relationships and suggests ways emotional intelligence can be used in science education.